Community broadcasting and mental health: The role of local radio and television in enhancing emotional and social well-being. (1st November 2011) - MEADOWS, MICHAEL; FOXWELL, KERRIE
This article sets out to explore the role of community broadcasting in enhancing the emotional and social well-being of its diverse audiences. We argue that communitybased broadcasting is having a positive impact on the state of mental health of its audiences. We make our argument by reviewing audience research data from a study of the Australian community broadcasting sector conducted between 2004 and 2007. The findings reveal that the community radio and Indigenous television sectors are making a significant contribution to managing community mental health by empowering audiences to better understand and control issues that impact on their emotional and social well-being. This suggests opportunities for health care agencies to consider the potential of enlisting community broadcasting in future mental health campaigns. The study reinforces a claim that mainstream media need to be more aware of a growing dissatisfaction with their inability to 'connect' with their diverse audiences on such issues. It also provides further evidence for community radio as a key cultural resource that meets its expected outcomes in contributing to social gain.